2020
DOI: 10.1371/journal.pone.0229759
|View full text |Cite
|
Sign up to set email alerts
|

Brain function and metabolism in patients with long-term tacrolimus therapy after kidney transplantation in comparison to patients after liver transplantation

Abstract: Background About 50% of the patients 5-7 years after kidney transplantation show impairment of memory, attention and executive function. Tacrolimus frequently induces neurological complications in the first few weeks after transplantation. Furthermore, tacrolimus treatment is associated with impaired cognitive function in the long-term in patients after liver transplantation. We hypothesize that long-term tacrolimus therapy is associated with cognitive dysfunction and alterations of brain structure and metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 31 publications
0
16
0
4
Order By: Relevance
“…However, severe complications in the form of confusion, seizures, psychosis, cortical blindness, and coma are rare, affecting 1–6% of transplant recipients. Neurotoxicity is more common early after initiation of the drug, but can happen months or years later [8].…”
Section: Discussionmentioning
confidence: 99%
“…However, severe complications in the form of confusion, seizures, psychosis, cortical blindness, and coma are rare, affecting 1–6% of transplant recipients. Neurotoxicity is more common early after initiation of the drug, but can happen months or years later [8].…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, traditional risk factors such as ageing, comorbid disease, i.e., hypertension, diabetes mellitus, hypercholesterolemia, and nontraditional risk factors, i.e., chronic inflammation, oxidative stress, hypercoagulable state should also be taken into consideration [1,8,12]. Additionally, many studies reported that magnetic resonance imaging (MRI) of the brain in CKD patients, also young patients, show subclinical brain lesions like white matter hyperintensities, silent lacunar infarcts, microbleeds, and cerebral atrophy [13][14][15]. The prevalence of cognitive impairment in endstage renal disease patients has been estimated at 50%-80% [16,17].…”
Section: Cognitive Impairment In Chronic Kidney Diseasementioning
confidence: 99%
“…There have been far fewer studies assessing the long-term effects of kidney transplantation on cognition. Recently, Pflugrad et al [15] investigated cognitive function, brain structure, and metabolism in patients treated by standard-dose tacrolimus therapy 10 years after kidney transplantation. The control group consisted of kidney recipients 1 and 5 years after successful surgery, tacrolimus treated patients after liver transplantation and healthy controls.…”
Section: Cognitive Impairment In Kidney Transplant Recipientsmentioning
confidence: 99%
See 2 more Smart Citations